The objectives as core element of the curriculum: conceptions and practices of faculty in the introductory programming course at a Brazilian university (Research, Society and Development, 2022)
Studying the conceptions and practices of teachers regarding the objectives in the Introductory Programming (IP) course is a relevant topic in Higher Education, since the objectives should guide the teaching and learning process of a subject considered difficult to teach by demanding diverse skills from students. This work is part of a broader research project, whose data were collected from semi-structured interviews with 29 professors from a Brazilian university about their planning and classroom practices. Data were analyzed using content analysis with the NVivo software. Teachers' conceptions about the objectives of IP are, essentially, programming and developing programming logic in problem-solving, aligning activities with the practice of exercises that teachers believe lead to the development of cognitive skills. The objectives of the subject programs and the teachers' plans were also analyzed, concluding that, although most of the objectives are student-centered, all had problems in clarity and raised doubts at the cognitive level. The presented results are an opportunity to: promote reflections in the academic community about what the objectives that emerged from the interviews really mean; and discuss the feasibility of the objectives in terms of students' development and experience. It is essential to question the rationality underlying the formulation of objectives and how to operationalize it, since the minority of teachers have pedagogical training.